2012
DOI: 10.3354/ab00443
|View full text |Cite
|
Sign up to set email alerts
|

Microbial abundance in the coelenteron and mucus of the cold-water coral Lophelia pertusa and in bottom water of the reef environment

Abstract: Microorganisms play an important role in coral ecology; however, little is known about cold-water coral (CWC) reefs. Microbial abundance in bottom water of Lophelia pertusadominated CWC reefs in the Skagerrak, North Sea, was elevated by ca. 40% for prokaryotes and 70 to 90% for viruses compared to bottom water where no corals were present. This indicates that CWCs influence the microbial food web in bottom water. Furthermore, results suggest that microorganisms contributed significantly to the stock of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…This is an important mechanism which allows a switch from food ingestion to a removal of undesired components, such as food remnants, metabolites with high N content (Wild et al, 2008), sediment or other particles (Larsson et al, 2013;Larsson and Purser, 2011;Zetsche et al, 2016). Also, mucus has an important role in fuelling bacterial growth in the coelenteron (Herndl and Velimirov, 1986;Weinbauer et al, 2012) and the close vicinity of the coral environment (Wild et al, 2004a(Wild et al, ,b, 2008(Wild et al, , 2009(Wild et al, , 2005. In the light of the diverse role of mucus, a frequent switch between TOC excretion and uptake might be related to the direction of mucus flow transporting mucus-trapped TOC into (uptake) or out of the coelenteron (excretion), where for corals of the HF the more frequently observed TOC uptake might be a consequence of the more frequent food uptake and inward-directed ciliate and mucus movement.…”
Section: Function Of Mucusmentioning
confidence: 99%
“…This is an important mechanism which allows a switch from food ingestion to a removal of undesired components, such as food remnants, metabolites with high N content (Wild et al, 2008), sediment or other particles (Larsson et al, 2013;Larsson and Purser, 2011;Zetsche et al, 2016). Also, mucus has an important role in fuelling bacterial growth in the coelenteron (Herndl and Velimirov, 1986;Weinbauer et al, 2012) and the close vicinity of the coral environment (Wild et al, 2004a(Wild et al, ,b, 2008(Wild et al, , 2009(Wild et al, , 2005. In the light of the diverse role of mucus, a frequent switch between TOC excretion and uptake might be related to the direction of mucus flow transporting mucus-trapped TOC into (uptake) or out of the coelenteron (excretion), where for corals of the HF the more frequently observed TOC uptake might be a consequence of the more frequent food uptake and inward-directed ciliate and mucus movement.…”
Section: Function Of Mucusmentioning
confidence: 99%
“…The mucus of shallow-water scleractinian corals is subject to diurnal or hourly replacement cycles, and therefore its bacterial diversity and richness could be constantly changing (Ainsworth et al, 2010;Sweet et al, 2011). In the deep-water scleractinian Lophelia pertusa, bacterial communities within the tissues were more stable than those in mucus, which is continuously being replenished following release in the water column (Wild et al, 2008;Weinbauer et al, 2012). It has been previously documented that P. arborea produces abundant mucus (Etnoyer et al, 2006).…”
Section: Alpha and Beta Measures Of Bacterial Diversitymentioning
confidence: 99%
“…As only a few cold-water corals have been studied, there is a knowledge gap regarding these organisms' bacterial communities and their functional roles in the host. Previous studies have reported variability in bacterial compositions between octocoral genera (Brück et al, 2007), between congeners (Holm and Heidelberg, 2016;Kellogg et al, 2016), between coral microhabitats (Weinbauer et al, 2012), within species and between sampling locations (Gray et al, 2011). In this study, we characterized the bacterial associates of P. arborea across two compartments: (1) skeletal and polyp tissue, and (2) surface mucus, and examined the degree of similarity in bacterial composition across three study locations in the Gulf of Maine (ranging in depth between 411 and 700 m) to explore the effects of relative sampling location proximity and depth on bacterial composition.…”
Section: Introductionmentioning
confidence: 98%
“…However, we have no direct evidence for this to occur in the present study. Another recent study on cold water corals reported that an experimental enrichment of viral and bacterial abundance in surrounding water did increase the abundances in the coelenteron but not in the mucus of corals, indicating some sort of ecological stability of epibiotic microbes (Weinbauer et al 2012). Alternatively, coral-associated bacterial communities have also been recognized for their ecological adaptation, being capable of strong physiological and genetic adjustments to cope with environmental disturban ces and to ultimately ensure coral viability (Reshef et al 2006.…”
Section: Inter-site Comparison Of Viral and Bacterial Traits In Coralmentioning
confidence: 99%